Dual Control: Investigating the Role of Drone (UAV) Operators in TV and Online Journalism - Adams, Catherine (2020)
At a time when TV and online journalism embraces more moving images filmed from drones than ever before, this article seeks to explore the thoughts and actions of those who produce them. It builds on earlier research into how aerial images impact on the viewer through the lens of ‘quality journalism’ (Adams, 2018). It investigates how drone operators are involved in the journalistic process, what meanings and effects they seek and who controls their work in a market-driven environment. Qualitative analysis was carried out of seventeen in-depth interviews with drone operators, journalists and editors working in UK and around the world. Data revealed a high degree of creative freedom among the operators, a passion for using drones and some desire to immerse and impress the viewer. It showed that aerial images have become paramount in video journalism amid market pressures to find ever more sophisticated and ‘cinematic’ shots. Interviewees felt drones had been “good for journalism,” by providing raw data, exciting new perspectives, context and story-telling techniques and “space to think.” The article explores the significant yet often unplanned contribution to the journalistic process of the drone operator and recommends more is done to increase understanding between journalist and pilot, such as providing training courses designed to teach quality drone journalism, as the media approaches ‘peak drone.’